P.056 Optimizing IVIg Use for Neuromuscular Conditions in British Columbia, Canada – Targeting High and Chronic User Groups. (November 2021) - Chapman, K; Beauchamp, A; Moisa Popurs, M; Mosewich, R; Beadon, K
Abstract : Background: Neuromuscular conditions account for 1/3 of IVIg use in BC and costs over $10 million annually. Since 2013, the BC Neuromuscular Review Panel has developed diagnostic and treatment algorithms for the use of IVIg. A framework was created to review high dose and chronic users. Methods: Utilizing Central Transfusion Registry data, all patients treated with IVIg for approved neuromuscular conditions (CIDP, MG, MMN) since April 1, 2013 were identified. Annual cohorts for patients using higher than usual dose and chronic use (>3 years) were established, and evaluated annually. Patient specific recommendations were made. Results: The initial cohort identified 38 high users of 377 patients receiving IVIg. 27 appropriate, 9 "not appropriate". Subsequent cohorts showed a decrease in number of patients receiving inappropriate IVIg doses. In BC there has been a 36% increase in neuromuscular patients treated with IVIg (377 in 2013/14 to 512 in 2016/17). Despite this, IVIg the program has effectively reduced the annual grams/patient from 516 gm/patient in 2013/14 to 489 gm/patient in 2016/17. Conclusions: The BC Neuromuscular IVIg Review confirms that the majority of IVIg use is appropriate. Following yearly cohorts of chronic and high dose users helps optimize IVIg use, which may lead to improved patient care.